Risk Factors for Disability Upgrading Among Leprosy Patients During Treatment: Multilevel Modeling Analysis - Solomon Sisay Mulugeta MSc; Bezanesh Melese Maseresha MSc; Selamawit Getachew Wassihun MSc; Yikeber Abebaw Moyehodie MSc (SAGE Open Nursing, 2022)
Background Leprosy not only brings about bodily incapacity but also creates a nasty image of affected individuals, triggering discrimination and social stigma. The purpose of this study was to evaluate the status of leprosy disability in patients registered at the All African TB and Leprosy Rehabilitation and Training Center. Methods The study consists of 205 leprosy patients who were undergoing treatment at the All African TB and Leprosy Rehabilitation and Training Center from January 2015 to December 2019. Regional states of the patients were used as a clustering effect in the multilevel logistic regression model. Results In total, 205 (66.3%) completed records revealed patients with leprosy were disabled. Among these, 64.88% of them were males. In multilevel binary logistic regression analysis, the individual-level variables, such as median age (AOR = 1.1; 95% CI: 1.043, 1.13) of patients, patients with duration of symptom [7–12 months (AOR = 2.26; 95% CI: 1.50, 3.39), 13–24 months (AOR = 2.13; 95% CI: 1.44, 3.15), and more than 24 months (AOR = 2.67; 95% CI: 1.8, 4.02)], the absence of sensory loss (AOR = 0.84; 95% CI: 0.72, 0.96), and patients with asymmetry lesion distribution (AOR = 0.74; 95% CI: 0.65, 0.85), were the most significant determinant factors of disability. The default leprosy patient (AOR = 15.53; 95% CI: 1.82, 134.96) and new leprosy patient (AOR = 0.51; 95% CI: 0.33, 1.68) were the significant determinant factors of disability due to leprosy patients. Conclusion An individual-level factor on the risk of disability was higher as age increased and for patients with a longer duration of symptoms. The risk of disability was lower for patients who do not lose their sensation and for patients whose lesion distribution is asymmetrical. The community-level factor, patient categories, was also a significant factor in disability due to leprosy. Furthermore, programs should emphasize raising community awareness, focusing on key messages and early case detection campaigns, such as active surveys, as well as the availability of leprosy care in a public health facility.